2024
DOI: 10.3389/fnut.2023.1310345
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary inflammatory index and anemia in US adults

Huimiao Ma,
Wenqi Deng,
Haiyan Chen
et al.

Abstract: Background and aimsAnemia is a widespread global health concern, and recent research has unveiled a link between anemia and inflammation. The Dietary Inflammation Index (DII) is a novel tool used to assess the overall inflammatory potential of an individual’s diet. However, until now, there have been no studies demonstrating a connection between DII and anemia. This study aimed to explore the relationship between DII and the risk of anemia among Americans, as well as to examine the influence of other risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…DII has been shown in nutritional epidemiological research to correlate with levels of inflammatory and anti-inflammatory markers like IL-1β, IL-4, IL-6, IL-10, CRP, and TNF-α, predicting the connection between overall diet and these markers. [ 23 ] As recently documented in several studies, [ 11 , 24 ] the DII is strongly connected with RA and anemia. However, to our knowledge, no study has specifically investigated the correlation between DII and anemia in RA patients.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…DII has been shown in nutritional epidemiological research to correlate with levels of inflammatory and anti-inflammatory markers like IL-1β, IL-4, IL-6, IL-10, CRP, and TNF-α, predicting the connection between overall diet and these markers. [ 23 ] As recently documented in several studies, [ 11 , 24 ] the DII is strongly connected with RA and anemia. However, to our knowledge, no study has specifically investigated the correlation between DII and anemia in RA patients.…”
Section: Introductionmentioning
confidence: 76%
“…Reducing the intake of pro-inflammatory foods may be one of the effective measures to prevent the development of anemia. [ 11 ] Xiang et al discovered a positive correlation between DII and RA in Americans. They concluded that to prevent RA, simply eating anti-inflammatory foods is not enough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation